MRKNs: Gene, Functions, and Role in Disease and Infection - Wang, Tongtong; Liu, Wenqiang; Wang, Changfa; Ma, Xuelian; Akhtar, Muhammad Faheem; Li, Yubao; Li, Liangliang (Frontiers in Oncology, 2022)
The makorin RING finger protein (MKRN) gene family encodes proteins (makorins) with a characteristic array of zinc-finger motifs present in a wide array from invertebrates to vertebrates. MKRNs (MKRN1, MKRN2, MKRN3, MKRN4) as RING finger E3 ligases that mediate substrate degradation are related with conserved RING finger domains that control multiple cellular components via the ubiquitin-proteasome system (UPS), including p53, p21, FADD, PTEN, p65, Nptx1, GLK, and some viral or bacterial proteins. MKRNs also served as diverse roles in disease, like MKRN1 in transcription regulation, metabolic disorders, and tumors; MKRN2 in testis physiology, neurogenesis, apoptosis, and mutation of MKRN2 regulation signals transduction, inflammatory responses, melanoma, and neuroblastoma; MKRN3 in central precocious puberty (CPP) therapy; and MKRN4 firstly reported as a novel E3 ligase instead of a pseudogene to contribute to systemic lupus erythematosus (SLE). Here, we systematically review advances in the gene’s expression, function, and role of MKRNs orthologs in disease and pathogens infection. Further, MKRNs can be considered targets for the host’s innate intracellular antiviral defenses and disease therapy.